Frequency of Aspiration Pneumonia in Admitted Stroke Patients in Medical Wards of a Tertiary Care Hospital - Tariq Ullah; Zaman, Haidar; Halimur Rahman; Abdul Wajid (Indus Journal of Bioscience Research, 2025)
Background: Stroke is a leading cause of morbidity and mortality worldwide, often complicated by post-stroke medical conditions. Among these, aspiration pneumonia is one of the most serious and preventable complications, significantly worsening outcomes and increasing healthcare costs. Objective: To determine the frequency of aspiration pneumonia in stroke patients age more than 35 years. Methods: A descriptive cross-sectional study was conducted in the medical wards of Ayub Teaching Hospital, Abbottabad, over a period of three months, from February 2025 to May 2025. A total of 103 patients aged 35 years and above with ischemic or hemorrhagic stroke were enrolled through non-probability consecutive sampling. Patients with chronic pulmonary conditions or pneumonia due to causes other than stroke were excluded. Data were collected using a structured proforma, including demographic details, clinical features, comorbidities, and risk factors. The diagnosis of aspiration pneumonia was based on predefined clinical and radiological criteria. Data were analyzed in SPSS version 16.0, applying Chi-square and Fisher’s exact tests where appropriate. Results: Out of 103 patients, 18 developed aspiration pneumonia, giving a frequency of 17.5%. The risk was significantly higher among older patients (>65 years), those with dysphagia, nasogastric tube feeding, and reduced levels of consciousness (p